1985
DOI: 10.1016/0014-5793(85)81268-0
|View full text |Cite
|
Sign up to set email alerts
|

pH dependence of the S2 → S3 transition associated with O2 evolution in inside‐out thylakoids

Abstract: In inside-out vesicles, a large difference is observed in oxygen yield activity between pH 6.5 and 7.6 which is in contrast to right-side-out vesicles. The light saturation behaviour of the transition Sz + S1 also shows a pH dependence. In inside-out thylakoids, at pH 6.5, the light saturation curve of the S2 + SJ transitions exhibits 2 different light saturation processes whereas at pH 7.6 it resembles the light saturation behaviour of the other S-state transitions. This result is explained by the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The influence of quercetin on the oxygen flash yields of isolated control thylakoid membranes re-suspended in different buffers is presented on flash yields for control thylakoid membranes when the pH increases from 6.5 to 7.6 and more pronounced damping in alkaline pH (8.4), which is in accordance with previous findings that the oxygen-evolving capacity depends strongly on pH (Delrieu et al, 1985;Plijter et al, 1986). It can be seen that the addition of quercetin to thylakoid membranes at pH 6.5 and 7.6 leads to stimulation of the oxygen flash yields by about 35% and 13%, respectively.…”
Section: Effect Of Quercetin On the Oxygen Evolution Of Isolated Thylsupporting
confidence: 88%
“…The influence of quercetin on the oxygen flash yields of isolated control thylakoid membranes re-suspended in different buffers is presented on flash yields for control thylakoid membranes when the pH increases from 6.5 to 7.6 and more pronounced damping in alkaline pH (8.4), which is in accordance with previous findings that the oxygen-evolving capacity depends strongly on pH (Delrieu et al, 1985;Plijter et al, 1986). It can be seen that the addition of quercetin to thylakoid membranes at pH 6.5 and 7.6 leads to stimulation of the oxygen flash yields by about 35% and 13%, respectively.…”
Section: Effect Of Quercetin On the Oxygen Evolution Of Isolated Thylsupporting
confidence: 88%
“…7, bottom). This idea might be supported by a recent report (Delrieu et al 1985) which describes a decline of the $2 --+ $3 transition efficiency at alkaline pH in inside-out vesicles. However, as the effect already arises if the pH increases from 6.5 to 7.6 it probably relates to structural changes of the PS II donor side inferred from trypsin treatment experiments (V61ker and Renger 1984).…”
Section: Discussionmentioning
confidence: 67%
“…The dependence of transition probabilities on the S-state (Delrieu, 1974;Shinkarev and Wraight, 1993a,b), on flashnumber (Meunier and Popovic, 1989), or upon relaxation between flashes (Joliot and Kok, 1975;Meunier et al, 1996), were also frequently considered. Delrieu and Rosengard (1987) suggested that the classic Kok model should be extended to include flash-induced inactivation of the PSII, which is frequently observed experimentally (see e.g., Delrieu et al, 1985;Delrieu and Rosengard, 1987;Messinger et al, 1997). It is believed that many different factors are contributing to the observed effect, including the reduction of acceptor quinones influenced by the negative potential of the bare Pt-electrode and by electron balancing between photosystems.…”
Section: Introductionmentioning
confidence: 98%